Exploring the mechanism of Bu Zhong Yi Qi Tang in the treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) based on network pharmacology and molecular docking - Pengfei Zhou; Yang Xuan; Zaisheng Zhu; Han Wu; Yang Hu; Liangyou Chen; Qianya Zhou (Journal of Men's Health)
Background: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common and persistent condition affecting the male urinary system, with a global prevalence ranging from 2% to 10%. This study aims to investigate the therapeutic mechanisms of Bu Zhong Yi Qi Tang (BZYQT) in treating CP/CPPS using network pharmacology and molecular docking techniques. Methods: The active compounds and their corresponding target proteins of BZYQT were identified and screened using the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). Targets associated with CP/CPPS were determined through GeneCards, the Therapeutic Target Database (TTD), Online Mendelian Inheritance in Man (OMIM), and the Pharmacogenomics Knowledgebase (PharmGKB). Overlapping targets between BZYQT and CP/CPPS were analyzed using the STRING database to construct a protein-protein interaction (PPI) network. Key targets were further subjected to Gene Ontology (GO) functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Molecular docking studies were conducted to validate the interactions between core active compounds and key targets. In vitro experiments were performed to confirm the therapeutic efficacy of BZYQT in treating CP/CPPS. Results: The study identified 103 active compounds in BZYQT and 2064 potential target proteins. A total of 1020 CP/CPPS-related targets were retrieved from GeneCards, OMIM, TTD, and PharmGKB, leading to the identification of 73 overlapping targets and 5 core targets. GO enrichment analysis revealed that these targets are involved in inflammatory responses, apoptosis, oxidative stress, and cell proliferation. KEGG pathway analysis highlighted associations with pathways such as the ErbB signaling pathway. Molecular docking results suggested that kaempferol, an active compound in BZYQT, exhibited the highest binding affinity with the target proteins. Experimental validation demonstrated that kaempferol effectively inhibited the expression of EGFR, MMP9, TNF-α and IL-6. Conclusions: BZYQT exhibits significant therapeutic potential in the treatment of CP/CPPS through its multi-target and multi-pathway mechanisms. The active compound kaempferol plays a crucial role in alleviating pathological changes in CP/CPPS by downregulating the expression of MMP9, EGFR, IL-6, and TNF-α. These findings provide a molecular basis for the application of traditional Chinese medicine in the management of CP/CPPS.